FAKTOR-FAKTOR YANG MENYEBABKAN MENJADI ANAK JALANAN DI RAMAYANA PUSAT KOTA PEKANBARU - Putri Juwita; Elni Yakub; Khairiyah Khadijah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstrack: This study aims to determine the factors that cause street children in Ramayana Pekanbaru City Center. The subjects in this study were street children who were in the Ramayana shopping center of Pekanbaru City as informants, the researchers would conduct in researching the factors that led to being street children in the Pekanbaru city shopping center. Data collection techniques in this study were interviews, observation, and documentation. The data analysis techniques used in this study are data collection, data reduction, data display, and conclusion drawings. The factors that cause street children to become street children are related to what are the basic reasons for street children to take to the streets. Based on the results that have been carried out, namely